MODEL HOTEL BASED ON THE LEARNING OF HIS MAJESTY'S PRINCIPLES - Hutayon, Ratchuma; Methiyothin, Suchanee (Journal of Graduate School of Commerce-Burapha Review, 2020)
The study collects qualitative data by conducting in-depth interviews with the executives of four hotels which were once decorated by the Office of the Royal Development Projects Board Quantitative data is gathered from 18 experts and scholars using the Delphi Technique. Most of the respondent pool are male, over the age of 50, hold a bachelor’s or a master’s degree and have over 10 years of experience working on His Majesty the King’s working principles. The findings indicate that the model hotel for the learning of His Majesty the King’s working principles should: 1) apply acquired knowledge systematically; 2) nurture staff’s pride; 3) consistently hone staff’s observational skills in order for them to detect and solve problems quickly; 4) be committed to improving its work process and workflow; 5) promote its local identity; 6) implement a holistic approach to learn His Majesty the King’s working principles; 7) define its organizational structure as needed; 8) be economical with its use of resources; 9) streamline its service delivery so as not to affect the environment; 10) centralize its services; 11) operate on the principle that nature helps nature; 12) apply the “right the wrong” principle 13) foster staff and customers’ appreciation for nature; 14) share its resources with locals so as to improve their quality of live; 15) economize on its operational costs with self-reliance; 16) keep a balance between revenue and expenditure; 17) not invest beyond its financial capacity; 18) follow the administrative principle of self-sufficiency; 19) be honest, truthful and, sincere with customers and the local community; 20) work happily; 21) set goals together to create its own organizational culture and workplace.